(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
In this paper, we introduce Regular Interval-Valued Intuitionistic Fuzzy Graphs (RIVIFG) and investigate some of their attributes. We talk about some conditions for regularity of an interval-valued intuitionistic fuzzy graph and obtain \(f\)-morphism on an interval-valued intuitionistic fuzzy graph and regular interval-valued intuitionistic fuzzy graph. \((2, k)\)-regular and totally \((2, k)\)-regular interval-valued intuitionistic fuzzy graphs are some elegant properties.